Exploring The Elements of Batuan Painting as a Basis for Architectural Design Method - I Gusti Ngurah Arya Suryawan Putra; Paramita Atmodiwirjo; Rini Suryantini (Center for Scientific Publication, 2023)
This paper aims to identify elements of Batuan painting, a local Balinese painting, that potentially become the basis of the architecture design method. The explorations of painting become an alternative in developing design methods as explored by some architects, such as Zaha Hadid, Van Doesburg, and Gerrit Thomas Rietveld. Arguably, such approaches offer different insights into programming architecture and further enrich the design process by creating particular relations with the context, instead of producing a generic and contextless architecture. In this study, the local Batuan painting that is related closely to the daily life of the Balinese community and local philosophy is explored as an attempt to relate architecture with the locality and cultural identity as part of the design process. This study employs the qualitative approach by visual observations and content analysis of Batuan paintings, identifying the elements, compositions, and important aspects that are always present in Batuan paintings. This study reveals that there are three elements from Batuan painting that are essential for the design method, namely heterogeneity, hierarchy, and the particular local painting techniques of ngucek-ngurek-ngabur. Such elements were particularly developed by the painters from Batuan Village to represent the everydayness of the local society to Tri Hita Karana, Hulu-Teben, and Tri Mandala philosophy. Furthermore, the elements imply further the spatial classifications of local activities, dualism principles, and the embedded relationship between humans, humans with nature, and humans with God. The painting elements insinuate further insights for the basis of developing the architecture, particularly in the formal and spatial arrangements as well as spatial qualities, which could be more culturally meaningful and contextually situated.